1996
DOI: 10.1021/tx960003i
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Protein Model for Human Cytochrome P450 2D6 Based on the Crystal Structures of P450 101, P450 102, and P450 108

Abstract: Cytochromes P450 (P450s) constitute a superfamily of phase I enzymes capable of oxidizing and reducing various substrates. P450 2D6 is a polymorphic enzyme, which is absent in 5-9% of the Caucasian population as a result of a recessive inheritance of gene mutations. This deficiency leads to impaired metabolism of a variety of drugs. All drugs metabolized by P450 2D6 contain a basic nitrogen atom, and a flat hydrophobic region coplanar to the oxidation site which is either 5 or 7 A away from the basic nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 77 publications
(251 reference statements)
0
75
1
Order By: Relevance
“…Such calculations can be performed with very large numbers of molecules to act as a molecule selection filter. Comparative molecular fields analysis and pharmacophore approaches have been used to model P450 enzymes involved in drug metabolism and which have a role in important drug-drug interactions (de Groot et al, 1996(de Groot et al, , 1999aJones et al, 1996;Ekins et al, 2001). Recursive partitioning methods have been used extensively with large sets of molecules and either continuous (Chen et al, 1998(Chen et al, , 1999 or binary data for therapeutic target endpoints and P450 inhibition (Ekins et al, 2003a) and toxicity properties such as Ames mutagenicity status (Young et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Such calculations can be performed with very large numbers of molecules to act as a molecule selection filter. Comparative molecular fields analysis and pharmacophore approaches have been used to model P450 enzymes involved in drug metabolism and which have a role in important drug-drug interactions (de Groot et al, 1996(de Groot et al, , 1999aJones et al, 1996;Ekins et al, 2001). Recursive partitioning methods have been used extensively with large sets of molecules and either continuous (Chen et al, 1998(Chen et al, , 1999 or binary data for therapeutic target endpoints and P450 inhibition (Ekins et al, 2003a) and toxicity properties such as Ames mutagenicity status (Young et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We first observed that the extrahepatic CYP1A1 occurred predominantly in the cytosol and that only its cytosolic enzymatic activity, measured as 7-ethoxyresorufin-deethylation, could be enhanced by addition of hematin (8 M), presumably by reconstitution of apocytochrome. Soluble P450s are known to be present in bacteria (de Groot et al, 1996) and yeast (Yang et al, 1997). Mammalian P450s also can occur in soluble form when truncated at the N-terminal membrane anchor, although with impaired biological activity (Kempf et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Structural information of CYP2D6 from homology models (de Groot et al, 1996;De Rienzo et al, 2000) and a crystal structure of ligand-free CYP2D6 (Rowland et al, 2006) revealed two acidic amino acids, Glu216 and Asp301, and two phenylalanine residues, Phe120 and Phe483, in the active site cavity. This was compatible with the previous pharmacophore models identifying the basic nitrogen and a planar hydrophobic area as characteristic features in CYP2D6 substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the early pharmacophore models are rather crude, they have been successful in predicting the influence of CYP2D6 in the metabolism of xenobiotics as well as predicting possible sites of metabolism [e.g., 75% predictability (de Groot et al, 1999)]. Structural information of CYP2D6 from homology models (de Groot et al, 1996;De Rienzo et al, 2000) and a crystal structure of ligand-free CYP2D6 (Rowland et al, 2006) revealed two acidic amino acids, Glu216 and Asp301, and two phenylalanine residues, Phe120 and Phe483, in the active site cavity. This was compatible with the previous pharmacophore models identifying the basic nitrogen and a planar hydrophobic area as characteristic features in CYP2D6 substrates.…”
mentioning
confidence: 99%